Government pay policies in Ceylon - International Labour Office (Geneva : International Labour Office, 1971)
This book provides the background necessary for a better understanding of the pay policies of the Ceylon Government and their role in the economic life of the country.
Includes bibliographical references.
hza 21/02/2019
Loan
Keywords: Sri Lanka